KASA IS A PROFESSIONAL DEVELOPMENT PROGRAM FOR FOREIGN LANGUAGE TEACHERS IN UZBEKISTAN (International Scientific Journal Alfraganus, 2026)
Teaching competences take many forms and vary in content depending on the environment and subject area. As a result, English language teachers need to simplify and systematize their teaching competences to a certain extent. This article defines these competences in a broad sense, including teaching, students and learning, language and culture, educational institutions, society, and professional life.
Keywords: competences; culture; identity; KASA; professional development; reflexive skills